Peningkatan Hasil Belajar Melalui Model Pembelajaran Window Shopping pada Materi Alat Pernapasan Manusia dan Hewan - Ningsih, Dwi Ratna; Nurhidayah, Nurhidayah; Trisnawati, Oky Ristya (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
This study aims to describe the application of the window shopping learning modelimproves learning outcomes in class V human and animal respiratory material at MIGiwangretno for the 2021/2022 academic year and to find out the increase in learningoutcomes in class V human and animal respiratory material at MI Giwangretno2021/2022. This research is a Classroom Action Research (CAR) through qualitativemethods which was carried out in class V MI Giwangretno with a total of 26 studentsconsisting of 15 boys and 11 girls. Researchers used data analysis in the form ofquantitative and qualitative data analysis. The data analysis technique used is datareduction, data presentation, and drawing conclusions. The results of the study found thatthe application of the window shopping learning model to material on human and animalbreathing apparatus in class V MI Giwangretno was carried out according to the scenariothrough the pre-cycle, cycle I, and cycle II stages and the window shopping learning modelwas proven to be able to improve student learning outcomes in the cognitive domain.affective, and psychomotor. This can be seen from the learning outcomes in the cognitivedomain, namely the average class value which was previously 69.03 increased to 73.37 incycle I, and in cycle II it increased to 86.26 and the percentage of completeness of learningoutcomes increased from 53.85% to 69.23% in cycle I, and increased to 92.31% in cycleII. Learning outcomes in the affective domain, namely an increase in students in the goodcategory, initially 9 students became 14 students in cycle I, and in cycle II it became 20students, while learning outcomes in the psychomotor domain can be seen from the numberof students who are able to make works that are displayed creatively and interesting andcan be completed on time, namely in the first cycle there are 16 students increased to 26students in the second cycle